2005
DOI: 10.1103/physrevb.72.125332
|View full text |Cite
|
Sign up to set email alerts
|

Disorder suppression and precise conductance quantization in constrictions of PbTe quantum wells

Abstract: Conductance quantization was measured in submicron constrictions of PbTe, patterned into narrow,12 nm wide quantum wells deposited between Pb0.92Eu0.08Te barriers. Because the quantum confinement imposed by the barriers is much stronger than the lateral one, the one-dimensional electron energy level structure is very similar to that usually met in constrictions of AlGaAs/GaAs heterostructures. However, in contrast to any other system studied so far, we observe precise conductance quantization in 2e 2 /h units,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…All these findings prove the efficiency of the dielectric screening of the Coulomb potentials caused by various defects existing in the vicinity of the conducting channel. This conclusion has been supported by the model calculations [12]. It is also worth noting here that we have not observed the "0.7" feature at the lowest conductance plateau [27], most probably due to the effective screening of the electron-electron interaction in PbTe.…”
Section: Quantum Ballistic Transportsupporting
confidence: 76%
See 2 more Smart Citations
“…All these findings prove the efficiency of the dielectric screening of the Coulomb potentials caused by various defects existing in the vicinity of the conducting channel. This conclusion has been supported by the model calculations [12]. It is also worth noting here that we have not observed the "0.7" feature at the lowest conductance plateau [27], most probably due to the effective screening of the electron-electron interaction in PbTe.…”
Section: Quantum Ballistic Transportsupporting
confidence: 76%
“…In fact, detailed studies of the single constriction geometry have shown that the step heights correspond to the quantized values within an accuracy of a few percent. This means that the electron transmission is close to 1, even at zero magnetic field [12]. A further evidence of weak disorder in PbTe constrictions has been found by conductance measurements in a millikelvin temperature range.…”
Section: Quantum Ballistic Transportmentioning
confidence: 64%
See 1 more Smart Citation
“…Previously it had been shown [35][36][37] that quantum Hall effect can be observed in such molecular beam epitaxy grown PbEuTe/PbTe/PbEuTe structures, i.e., edge channel transport was demonstrated for applied magnetic fields. Furthermore, in narrow constrictions fabricated from such/PbTequantum wells embedded in PbEuTe barriers our group has reported precise zerofield conductance quantization in units of 2e 2 =h [38,39]. We demonstrate that electron transport measurements on H-shaped microstructures do not show any nonlocal resistance in this case.…”
mentioning
confidence: 78%
“…Because of the [111] growth direction, the fourfold L-valley degeneracy of the conduction band in PbTe QW is lifted by the quantum confinement, so that the ground-state two-dimensional (2D) subband is formed of the single valley with its main axis parallel to the growth direction [38]. The lowest states formed by the three remaining valleys obliquely oriented to the growth directions, have a higher energy of 35 meV above the ground state for this QW thickness.…”
mentioning
confidence: 99%